Appraisal of Fizzling Features of Hausa Vernacular Architecture (HVA) in Selected Areas of Jos (cikin gari) City Centre, Plateau State, Nigeria. - Jolaoso, Babatunde Adekoyejo; Bello, Muhammad Murtala; Umaru, Auwalu Nasir; Adamu, Sani Tal (University of Merdeka Malang, 2023)
Dakali is a unique feature that plays a functional role in the Hausa Vernacular Architecture (HVA). However, events have revealed a gradual extinction from the streetscape due to contemporary changes in the cityscapes and the general physical development with the concomitant effect of reduction in the performance of the expected function in buildings. This paper focuses on the enumeration and documentation of buildings with or without this significant feature. It also appraises the attendant contemporary architectural design-shift. The paper adopts quantitative research approach; purposive sampling and Content analysis method in the selection of potential respondents and review of related literature respectively. This was complimented with the conduct of field survey, selective interviews and observation. Information extracted therefrom was descriptively presented. Findings revealed that out of the total of 235 selected samples, 50 buildings (about 21%) reflects the HVA features; only 14 buildings (about 5.95%), though with retained feature HVA like the Dakali, but have significantly lost the features and transiting towards the contemporary/modern trends; while, 171 (about 72.7%) of the buildings in the study area have completely been transformed. The paper concludes that there is the need for the identification and comprehensive documentation other HVA features for posterity, so as not to allow their total loss without any form of record of their historical existence, due to fast changes been experienced arising from the advent of innovative design, challenges of rapid rate of global urbanization and the trending break-through in technological advancement within our urban/city settings.